1983
DOI: 10.1677/joe.0.0990063
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal changes in the immature rat after administration of pregnant mare serum gonadotrophin: influence of body weight

Abstract: We have shown previously that pregnant mare serum gonadotrophin (PMSG) induces ovulation only in rats weighing over 60 g on the day of injection. The under-60 g rats do not ovulate although they secrete a preovulatory surge of a pleiomorphic form of LH. Presumably this pleiomorph is inactive. Comparisons were made of plasma hormone concentrations in rats treated with PMSG that weighed over and under 60 g. The measurements were made on samples taken between 13.00 and 22.00 h on the day of the expected preovulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The pattern of metabolism in the 20-day-old normal and 70-day-old hpg animal may, therefore, represent that of the testis undergoing minimal bioactive gonadotrophin stimulation. The changes which occur in the normal animal between 20 and 40 days may be related to a number of fac¬ tors such as circulating levels of gonadotrophins (Ketelslegers, Hetzel, Sherins & Catt, 1978), growth hormone (Ojeda & Jameson, 1977), body core tem¬ perature (Wilson, Buckingham & Morris, 1985), pro¬ portion of body fat (Wilson, ter Haar, Bonney et al 1983) or testicular descent which occurs at this time in the mouse. The pattern of pregnenolone metabolism in the 20-to 25-day-old hpg mouse is unlike that of any age of postnatal animal.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of metabolism in the 20-day-old normal and 70-day-old hpg animal may, therefore, represent that of the testis undergoing minimal bioactive gonadotrophin stimulation. The changes which occur in the normal animal between 20 and 40 days may be related to a number of fac¬ tors such as circulating levels of gonadotrophins (Ketelslegers, Hetzel, Sherins & Catt, 1978), growth hormone (Ojeda & Jameson, 1977), body core tem¬ perature (Wilson, Buckingham & Morris, 1985), pro¬ portion of body fat (Wilson, ter Haar, Bonney et al 1983) or testicular descent which occurs at this time in the mouse. The pattern of pregnenolone metabolism in the 20-to 25-day-old hpg mouse is unlike that of any age of postnatal animal.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a clearly raised LH concentration in hCG-treated rats com¬ pared with those in saline-treated controls on the after¬ noon of day 31 (pro-oestrus) shows this convinc¬ ingly. Perhaps differences in levels of growth hormone, corticosterone or prolactin (Wilson et al 1983) account for differences in follicle responsiveness and cause the differences in number of ova shed between rats of lower and higher body weight as found in the present study. It seems less likely that the number of small antral follicles present in the ovary at the start of hCG treatment would be a limiting factor, since in younger animals (i.e.…”
Section: Discussionmentioning
confidence: 52%
“…It thus seems that the rats with a low body weight on day 28 are less capable of maturation of antral follicles towards the preovulatory stage. A body weightdependent reaction to gonadotrophin treatment of im¬ mature rats was also reported by Wilson, ter Haar, Bonney et al (1983) using pregnant mare serum gonadotrophin. However, these authors found occur¬ rence of ovulation in rats over 60 g and absence of follicle rupture and ovulation in rats weighing less than 60 g. They suggested that the occurrence of a pleio¬ morphic, inactive LH surge could be held responsible for the lack of ovulation.…”
Section: Discussionmentioning
confidence: 53%
“…On the day of the pre-ovulatory LH surge, the under 60 g PMS-treated rat has significantly lower plasma levels of corticosterone, prolactin and GH compared to age-matched heavier controls (Wilson et al 1983). Administration of ACTH, corticoster¬ one and GH stimulate ovulation in the under 60 g group without stimulating extra LH release and appear to convert the biologically abnormal LH form to one that can be detected by the cytochemi¬ cal bioassav .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the PMS-treated rats weighing less than 60 g (<60 g) secrete lower levels of prolactin, corticosterone and growth hormone (GH) compared to similarlytreated heavier rats (Wilson et al 1983). However, the ovaries of the lighter rats appear to respond normally toward exogenous gonadotrophins (Wil¬ son et al 1985).…”
mentioning
confidence: 99%